Poly(ADP-ribose)polymerase 2 is zinc-dependent enzyme and nucleosome reorganizer - Natalya Maluchenko; Alexandra Saulina; Olga Geraskina; Elena Kotova; Anna Korovina; Grigoriy Armeev; Mikhail Kirpichnikov; Alexey Feofanov; Vasily Studitsky (Cellular and Molecular Life Sciences)
Abstract Poly(ADP-ribose)polymerase 2 (PARP2) is a nuclear protein, DNA damage sensor and an emerging target for development of anti-cancer drugs. Previously it was discovered that PARP2 binds to nucleosomes; however, critical factors involved in this process remain unknown. We demonstrated that in the presence of Mg2+ or Ca2+ ions PARP2 forms complexes with a nucleosome containing different number of PARP2 molecules without altering conformation of nucleosomal DNA. In contrast, Zn2+ ions directly interact with PARP2 inducing a local alteration of the secondary structure of the protein and PARP2-mediated, reversible structural reorganization of nucleosomes. WGR domain of PARP2 is the target for Zn2+ ions since this domain contains two putative Zn2+−binding sites, binds Zn2+ ions and alone drives Zn2+-mediated reorganization of nucleosomes. Auto(poly-ADP-ribosylation) activity of PARP2 is enhanced by Mg2+ ions and modulated by Zn2+ ions: suppressed or enhanced depending on the occupancy of two functionally different zinc binding sites. The data suggest that transient changes in concentration of cations can differentially modulate PARP2 activity, local chromatin structure and the DNA damage response. Graphical abstract